PENGARUH PENINGKATAN RASIO KONSENTRAT DALAM RANSUM KAMBING PERANAKAN ETTAWAH DI LINGKUNGAN PANAS ALAMI TERHADAP KONSUMSI RANSUM, RESPONS FISIOLOGIS, DAN PERTUMBUHAN - Qisthon, Arif; Widodo, Yusuf (Universitas Sam Ratulangi, 2015)
ABSTRACT EFFECTS OF INCREASING CONCENTRATE RATIO IN THE RATION OF PERANAKAN ETTAWAH GOAT UNDER NATURAL HEATÂ ENVIRONMENT ON FEED INTAKE, PHYSIOLOGICAL RESPONSES, AND GROWTH. The research was conducted to study the effect of increasing the proportion of concentrate in the ration of Peranakan Ettawah (PE) goats. Animals were maintained in a natural hot environment on feed consumption, physiological responses, and body weight gain. The study used three male goats of PE in Latin Square design. Treatment applied was an increase in the proportion of concentrate in three forage-concentrate ratio (F:C), R1 = 85:15%; R2 = 70:30%; and R3 = 55:45%. The results showed that the treatment ratio of F:C had no effect (P> 0.05) in feed intake, respiration rate, rectal temperature, and body weight gain. In contrast, treatment affected significantly (P <0.05) heart rate, as follows R1 vs. R2 and R1 vs. R3, whereas R2 and R3 were not significantly different (P> 0.05). Keywords: Rations, heat stress, physiological, goat